Targeted next generation sequencing and family survey enable correct genetic diagnosis in CRX associated macular dystrophy - a case report - Al-Khuzaei, S; Hudspith, KAZ; Broadgate, S; Shanks, ME; Clouston, P; Németh, AH; Halford, S; Downes, SM (BioMed Central, 2021)
Background We present 3 members of a family with macular dystrophy, originally diagnosed as Stargardt disease, with a significantly variable age at onset, caused by a heterozygous mutation in CRX. Case presentation A 43-year-old female with bull’s eye maculopathy, whose sister was diagnosed with Stargardt disease previously at another centre, was found to have a single ABCA4 variant. Further examination of the family revealed that the asymptomatic father was also affected, indicating a dominant pattern of inheritance. In addition, the ABCA4 variant was not identified in the sister originally diagnosed with Stargardt disease. Next generation sequencing identified a heterozygous c.121C > T, p.R41W missense mutation in CRX in all 3 affected members. Conclusions We describe a common phenotype, but with variable age at onset, with autosomal dominant inheritance and reduced penetrance in a family found to have a pathogenic sequence variant in CRX. This illustrates the importance of panel based molecular genetic testing accompanied by family studies to establish a definitive diagnosis.